2018
DOI: 10.1155/2018/9139786
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anti-Inflammatory Activity, and In Silico Study of Novel Diclofenac and Isatin Conjugates

Abstract: The design, synthesis, and development of novel non-steroidal anti-inflammatory drugs (NSAIDs) with better activity and lower side effects are respectable area of research. Novel Diclofenac Schiff's bases (M1, M2, M4, M7, and M8) were designed and synthesized, and their respective chemical structures were deduced using various spectral tools (IR, 1H NMR, 13C NMR, and MS). The compounds were synthesized via Schiff's condensation reaction and their anti-inflammatory activity was investigated applying the Carrage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Furthermore, the lead finder program [69] on Cresset flare software [23] is characterized by the combination between the genetic algorithm and different optimization strategies leading to great efficiency, robustness, accuracy, and speed of calculations [69]. Musab Ibrahim et al [77] found the results of a molecular docking study about novel synthesized COX enzyme inhibitors conducted in Cresset Flare software were aligned with results of the conducted in vivo study. Depending on that, the obtained results of the predicted targets could be with considerable accuracy.…”
Section: -D-alanine D-alanine Ligase Enzymementioning
confidence: 99%
“…Furthermore, the lead finder program [69] on Cresset flare software [23] is characterized by the combination between the genetic algorithm and different optimization strategies leading to great efficiency, robustness, accuracy, and speed of calculations [69]. Musab Ibrahim et al [77] found the results of a molecular docking study about novel synthesized COX enzyme inhibitors conducted in Cresset Flare software were aligned with results of the conducted in vivo study. Depending on that, the obtained results of the predicted targets could be with considerable accuracy.…”
Section: -D-alanine D-alanine Ligase Enzymementioning
confidence: 99%
“…Initially, adamantane-1-carboxylic acid (9) was subjected to esterification (Scheme 1) to afford methyl adamantane-1-carboxylate (10) in good yield (85%). Subsequent reaction of 10 with hydrazine hydrate under reflux condition (Scheme 1) provided adamantane-1-carbohydrazide (11) in excellent yield (98%) [27,28]. e 5-substituted isatin derivatives 12-14 are commercially available, while the key intermediates 15 and 16 were yielded by treatment of 12 and 13 with 37% formalin under reflux conditions and were obtained in 50% yield [29].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, intermediate 17 (62%) was derivatized through alkylation of 5-bromoisatin (13) with benzyl chloride in DMF at 80°C using catalytic amount of potassium carbonate [29]. Finally, the designed Schiff bases (18-23) (47-82%) were prepared following the synthetic route depicted in Scheme 2 via condensation of adamantane-1-carbohydrazide (11) with the appropriate isatin derivative (12)(13)(14)(15)(16)(17) according to a reported procedure [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that isatin derivatives, which possess electron withdrawing groups such as halogens, at the C5 or C7 position exhibit remarkable anti-inflammatory activity (23,24). Thus, it is also possible to suggest that the anti-inflammatory activity of COPHCT may be attributed to the presence of the chlorine in C5 position in the structure.…”
Section: Discussionmentioning
confidence: 99%